The experience of preparing for and transitioning to registered practice. (28th March 2019) - Hart, Elizabeth
Abstract : Background: over the past 10 years higher education institutions (HEIs) have redeveloped their nursing courses so that students follow a degree-level programme. The curriculum requires 50% of the total learning hours to be clinically based. This includes placements within the final year to assess management skills. Aims: this study focuses on exploring retrospective experiences of learning and support within the final placements, as reflected upon by newly qualified nurses in one trust. Method: phenomenological one-to-one interviews were used, and data were analysed using Colaizzi's method. Findings: the study found a positive experience of placements. The level of support final-placement students experienced was found to be dependent on staffing levels, commitment from staff and their passion for teaching. Placements were found to support preparation for practice. The impact of familiarity with a trust in improving transition was also recognised. Conclusion: this study recommends supporting transition through targeted placements based on employment, solid links between the HEI and trusts and increased support and teaching for students.